N‐Glycan Engineering: Constructing the N−GlcNAc Stump. (7th September 2022) - Wu, Qifan; Dong, Suwei; Xuan, Weimin
Abstract: N‐Glycosylation is often essential for the structure and function of proteins. However, N‐glycosylated proteins from natural sources exhibit considerable heterogeneity in the appended oligosaccharides, bringing daunting challenges to corresponding basic research and therapeutic applications. To address this issue, various synthetic, enzymatic, and chemoenzymatic approaches have been elegantly designed. Utilizing the endoglycosidase‐catalyzed transglycosylation method, a single N‐acetylglucosamine (N‐GlcNAc, analogous to a tree stump) on proteins can be converted to various homogeneous N‐glycosylated forms, thereby becoming the focus of research efforts. In this concept article, we briefly introduce the methods that allow the generation of N‐GlcNAc and its close analogues on proteins and peptides and highlight the current challenges and opportunities the scientific community is facing. Abstract : A single N‐GlcNAc residue on proteins can be converted to various homogeneous N‐glycosylated forms by endoglycosidase‐catalyzed transglycosylation. This represents a very powerful strategy for N‐glycan engineering. In this concept article, methods that allow the generation of N‐GlcNAc and its close analogues on proteins and peptides are summarized and discussed.